Pengelolaan Sampah Terpadu untuk Kelestarian Lingkungan dan Peningkatan Ekonomi Masyarakat Desa - Mohammad Rosyada; Tedi Sigit Pramono; Wildana Liziaroti; Nur Intisah; Muhammad Falih Zuhaid; Oktavia Maulatul Mu’tiqoh (Ngarsa: Journal of Dedication Based on Local Wisdom, 2025)
Waste is a critical issue in Sidomulyo Village, Pekalongan Regency, primarily due to the absence of a designated disposal facility. As a result, residents dispose of waste by burning or burying it, causing environmental pollution, public health risks, and long-term ecological damage. To address this, a waste bank initiative was introduced to promote sustainable waste management and increase community awareness. The waste bank serves not only as a means of processing waste but also as an educational tool to encourage environmental responsibility through the 3R principles: reduce, reuse, and recycle. The program employed the Asset-Based Community Development (ABCD) approach, focusing on empowering local resources and capacities. Activities included community engagement, village clean-up with waste separation, and seminars on waste bank management. Findings indicate a significant increase in public awareness regarding household waste management. Moreover, the waste bank has contributed positively to both environmental cleanliness and household economic improvement. This model demonstrates that participatory and asset-based approaches can effectively promote sustainable waste solutions in rural communities. Keywords: Waste bank, Environmental sustainability, Economic empowerment  Abstrak: Sampah merupakan masalah serius di Desa Sidomulyo, Kabupaten Pekalongan, yang disebabkan oleh belum tersedianya tempat pembuangan sampah. Akibatnya, masyarakat membuang sampah dengan cara dibakar atau ditimbun, yang berdampak pada pencemaran lingkungan, risiko kesehatan, dan kerusakan ekologis jangka panjang. Untuk mengatasi hal ini, program bank sampah diperkenalkan guna mendorong pengelolaan sampah berkelanjutan serta meningkatkan kesadaran masyarakat. Bank sampah tidak hanya berfungsi sebagai sarana pengolahan sampah, tetapi juga sebagai alat edukatif untuk menumbuhkan tanggung jawab lingkungan melalui prinsip 3R: reduce, reuse, dan recycle. Program ini menggunakan pendekatan Asset-Based Community Development (ABCD) yang berfokus pada pemberdayaan potensi lokal. Kegiatan meliputi pendekatan komunitas, kerja bakti pemilahan sampah, dan seminar pengelolaan bank sampah. Hasil menunjukkan peningkatan kesadaran masyarakat terhadap pentingnya pengelolaan sampah rumah tangga. Selain menjaga kebersihan lingkungan, bank sampah juga memberikan kontribusi positif terhadap peningkatan ekonomi keluarga. Model ini membuktikan bahwa pendekatan partisipatif dan berbasis aset efektif untuk solusi pengelolaan sampah di wilayah perdesaan. Kata kunci: Bank sampah, Kelestarian lingkungan, Peningkatan ekonomi